The Effect of Professionalism, Integrity, Motivation and Locus of Control on Audit Quality - Sadani, Ni Nyoman Ayu Juniari Purnama (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Audit quality is the result of the auditor's work as indicated by an audit report in accordance with the standards. The audit quality of the inspectorate apparatus shows the performance of the inspectorate apparatus in supervising regional finances. This study aims to examine the effect of professionalism, integrity, motivation, and locus of control on the audit quality of the inspectorate apparatus in regional financial supervision. The study was conducted at the Bangli Regency Inspectorate. The number of samples in this study were 41 people (Bangli Regency Inspectorate apparatus). Samples were selected using purposive sampling technique. Data was collected by distributing questionnaires to respondents. Data analysis technique used is multiple linear regression. The results showed that professionalism, integrity, and locus of control had a positive effect on the audit quality of the inspectorate apparatus in regional financial supervision. The results of this study were able to confirm agency theory and attribution theory.